Urinary tract infection after urodynamic study in HUSM, Kelantan - Mokhtar, Syamilah (2018)
Objective To determine the incidence of urinary tract infection after urodynamic study and to identify its risk factors Method: A prospective cross sectional study in Hospital Universiti Sains Malaysia was conducted from 1st March 2016 until 29th February 2017 (12 months).The study included 50 female patients who presented or referred to urogynecology unit HUSM for urodynamic study. Urine culture and sensitivity was collected during cathetherization before urodynamic study and repeat sample was collected after 4 to 7 days following procedure. The incidence of urinary tract infection was determined by the presence of growth in the urine culture post urodynamic study in the previously absence of growth in the urine culture before urodynamic study. To identify the risk factors for UTI, patient‘s clinical characteristics including age, menopausal state, parity, diabetic status, underlying neurological disorder, history of recurrent UTI and history of urological surgery were evaluated. The risk factors for UTI were analysed by using simple linear and multiple logistic regression. Results: A total of 50 patients were recruited in this study. The incidence of urinary tract infection after UDS was 8% (n). E.Coli is the most common identified organism (50%). Simple linear regression analysis demonstrated that underlying neurological disorder (p=0.029) and history of recurrent UTI (p=0.037) were the significant predictors of urinary tract infection. On multiple logistic regression none of the covariate are significant independent risk factors. Neurological disorder (p=0.098) and previous history of recurrent UTI (p=0.259). Elevated post void residual volume was associated with higher risk of developing UTI (p=0.022). The commonest pathogen post UDS was E. Coli (50%), followed by E. Coli ESBL (25%) and Group B Streptococcus (25%). E. Coli had shown complete sensitive to cefuroxime, however complete resistance to ampicilin and bactrim and partial resistance to augmentin. Meanwhile E. Coli ESBL was resistant to all common antibiotic tested. GBS was found to be sensitive to Penicilin G and erythromycin. Conclusion: The rate of UTI following UDS was low at 8%. The significant risk factors include underlying neurological disorder, previous history of recurrent UTI and elevated volume in post void residual urine.